2017
DOI: 10.1007/s12032-017-1015-1
|View full text |Cite
|
Sign up to set email alerts
|

High-dose 8% capsaicin patch in treatment of chemotherapy-induced peripheral neuropathy: single-center experience

Abstract: High-dose capsaicin patch is effective in treatment of neuropathic pain in HIV-associated neuropathy and diabetic neuropathy. There are no studies assessing effectiveness of high-dose capsaicin patch in treatment of chemotherapy-induced peripheral neuropathy. We sought to determine the effectiveness of treatment of pain associated with chemotherapy-induced peripheral neuropathy with high-dose capsaicin patch. Our study group consisted of 18 patients with clinically confirmed oxaliplatin-induced neuropathy. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
2
31
0
10
Order By: Relevance
“…A total of 282 articles were excluded during the eligibility assessment, and 25 additional papers were identified by scanning the reference lists. Therefore, 96 papers met the inclusion criteria and were used for this review [ 9 104 ]. These studies were published between 1980 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 282 articles were excluded during the eligibility assessment, and 25 additional papers were identified by scanning the reference lists. Therefore, 96 papers met the inclusion criteria and were used for this review [ 9 104 ]. These studies were published between 1980 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…In an open-label study, Filipczak-Bryniarska et al demonstrated that the high-dose capsaicin patch was effective in treating pain associated with oxaliplatin-induced neuropathy [ 104 ]. However, this finding should be interpreted with caution, given the limitations of the study design and small number of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Cannabis has demonstrated efficacy for neuropathic pain from peripheral neuropathy caused by HIV and diabetes, [130][131][132][133][134][135][136] but cannot be recommended for CIPN because of a lack of studies for this specific indication. Small quasi-experimental studies provide preliminary evidence that high-dose 8% capsaicin patches 137 and intravenous lidocaine 138 may ameliorate painful CIPN. However, larger studies with control group comparisons are needed to confirm or refute these preliminary findings.…”
Section: Pharmacologic Interventions: Clinical Studiesmentioning
confidence: 99%
“…Based on its effectiveness on the treatment of neuropathic pain in HIV-associated neuropathy and post-herpetic neuralgia, high-dose topical capsaicin was tested on the treatment of CIPN-associated pain. A single-centre trial, the application of high-dose capsaicin patch resulted in significant pain relief, without considerable adverse events [23]. In a sample of 18 colon cancer patients undergoing oxaliplatin-based chemotherapy, with painful peripheral polyneuropathy, there was an average pain score in approximately 84% to 97% patients after 12 weeks of application of capsaicin patch.…”
Section: High-dose 8% Capsaicin Patchmentioning
confidence: 99%